HUBUNGAN ANTARA SIKAP TERHADAP SAINS DENGAN HASIL BELAJAR FISIKA SISWA KELAS VIII SMPN 1 RETEH - Retno Irna Christina; Yennita '; Syaril ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research aims to determine students 'attitudes toward learning science in physics, know the score physics student learning outcomes and determine the relationship between students' attitudes toward science in the study of physics with a score of physics learning outcomes of students of class VIII SMPN 1 Reteh. The subject of this research is 157 students. This research used survey method for determine attitudes students toward learning science. Instrument used is questionnaire ratings attitude toward science that has 4 indicators. learning outcomes it comes from the score of exam results second semester of the school year 2016/2017 derived from teacher. The outcome assessment students' attitudes toward science are already on high-value category average score of 2.96. Scores of learning outcomes physics student at SMPN 1 Reteh VIII grade is high, as 75.16% of the samples are in the category of very high and high. While determinants coefficient (r2) 0,774 stated that 77.4% the learning outcomes of students in the classroom VIII physics SMPN 1 Reteh, determined by the students 'attitudes toward science Based on these results, it was concluded there was a positive relationship between students' attitudes toward science with physics student learning outcomes and student attitudes towards science affect the physics student learning outcomes by with amount correlation coefficient is 0,88 dan regression coefficient is 1,81.Keywords: Science Attitude, Relationshi, Learning Outcomes, Correlation, Regression.